Building Collective Power to Advance Maternal and Child Health Equity: Lessons from the New Orleans Maternal and Child Health Coalition - Johnson, Iman; Vilda, Dovile; Allen, Emma; Boisson, Desiree; Daniel, Clare; Giwa, Latona; Goldin Evans, Melissa; Ledet, Hali; Richardson, Lisa; Wallace, Maeve (Maternal and child health journal, 2024)
Objectives The New Orleans Maternal Child Health Coalition convenes to support and amplify the work of New Orleans-based individuals and organizations working to reduce disparities and protect the health of birthing families in the New Orleans area. The objectives of this qualitative study were to identify successes, challenges, and areas of growth for the Coalition and develop broadly generalizable recommendations for similar groups seeking to mobilize and advance health equity in their own communities. Methods Using purposive sampling, we conducted semi-structured interviews with 12 key informants from within and outside of the Coalition. Interviews were transcribed verbatim, and data was analyzed using inductive and deductive coding approaches. Results We identified themes relating to the barriers and facilitators to the maintenance of the Coalition, as well as opportunities to advance the mission of the Coalition. Some themes included structural- and systemic-level barriers to achieving the mission, varying perspectives on the effectiveness of the Coalition, opportunities to enhance the operations of the Coalition’s work, and opportunities to involve other individuals, particularly those with lived experience, and non-MCH related sectors in Coalition’s work. Conclusions for Practice As the maternal health crisis continues, coalitions like the New Orleans MCH Coalition provide a vehicle to amplify the mission-driven work of people and organizations. Recommendations put forth by the Coalition can also be utilized by coalitions in other jurisdictions. Significance What is Already Known on this Subject? Black–White disparities in maternal and child health (MCH) have a longstanding history within the United States (US) and these disparities are mirrored in New Orleans, LA. The New Orleans Maternal and Child Health Coalition was founded to support the collective efficacy of numerous individuals and organizations to protect the health of birthing families in the community. What Does this Study Add? We identified the key barriers and facilitators to achieving the Coalition’s mission and building collective power to achieve MCH equity in the greater New Orleans area. Such evidence is a crucial contribution during this time when rates of maternal mortality and morbidity continue to rise throughout the country. This study amplifies the importance of community-driven work to address disparities in MCH and enhance health equity.